Effects of Ion Characteristics on the Leaching of Weathered Crust Elution-Deposited Rare Earth Ore - Zhang, Zhenyue; Chi, Ru'an; Chen, Zhuo; Chen, Wendou (Frontiers in Chemistry, 2020)
To reveal the ion-exchange mechanism in the leaching process of weathered crust elution-deposited rare earth ores with different leaching agents, the effects of a variety of cations and anions at different concentrations on the leaching process were investigated, including Al3+, Fe3+, Ca2+, Mg2+, Na+, K+, NH4+ and Cl−, NO3-, and SO42-. Meanwhile, the relationships between different concentrations of cations and anions and leaching efficiency were investigated, as was the relationship between different concentrations of cations and anions and zeta potential. The effect of different ions on the swelling of clay minerals during leaching process was also investigated. The results shown that NH4+ was the most affected electrolyte cation in terms of rare earth leaching efficiency during the leaching process of weathered crust elution-deposited rare earth ore among three different cationic valence states, and the leaching efficiency was 86.93% at the optimal leaching concentration. The influence of the three anions on the leaching efficiency of rare earth was NO3->Cl->SO42-, and the leaching efficiency of rare earth were 83.21, 81.52, and 80.12% at the optimal leaching concentration, respectively. The NH4+ had the greatest effect on the zeta potential of weathered crust elution-deposited rare earth ore, and the zeta potential was −18.1 mV at the optimal leaching concentration. Additionally, the order of the effect of three anions on zeta potential was SO42->NO3->Cl-. Combined with the effect on the rare earth leaching process, anions and cations were considered separately, and NH4+ and Cl− were selected; the relationship between the rare earth leaching efficiency and zeta potential conforms to the follow equations: NH4+:Y = −0.48X2 – 13.51X – 1.58, R2 = 0.98133 and Cl−:Y= −1.22X2 – 17.64X + 23.29, R2 = 0.99010. It was also found in the swelling experiment of the weathered crust elution-deposited rare earth ore that the swelling ratio of clay minerals was the lowest when the cation and anion were NH4+ and Cl− and the swelling ratios were 1.874 and 2.015%, respectively.